PEMAHAMAN ISRO’ MI’ROJ DALAM AL-QURAN - Qutni, Darul; Damayanti, Nova Ayu (Universitas Negeri Semarang, 2021)
In the Qur ‟an, out of thousands of verses in it, there are only 4 verses that explain about Isrâ‟ Mi ‟raj, namely Q.S. Bani Isra`il Ayat 1, and Q.S. AnNajm Verses 13 to 15. That is, the greatness of Islam does not lie in the event of Isra ‟Mi‟ raj, but in its concept, system, and content. In Surat An-Najm Verses 13-15, it is described that Rasulullah met Jibril in his original form in Sidratil Muntaha during Isrâ` Mi ‟raj. Previously, Rasulullah also met the angel Jibril in his original form when he received the first verse (Q.S. Al-Alaq: 1-5) from Allah S.W.T., that is, when he was in the cave of Hira. The events of Isrâ '1 and Mi'râj are one of the miracles bestowed by Allah S.W.T. to His Messenger, Prophet Muhammad S.A.W., as a form of honor and consolation after his uncle and wife passed away. The event also served as a performer after his S.A.W. getting unfriendly treatment from the Thai population. This event is immortalized in the Qur ‟ân and Al-Hadith. Allah S.W.T. mentions this event in two places in the Qur`ân, namely Al-Isrâ ‟/17 Verse 1 and An-Najm/53 Verses 13-18. Dalam Al Qur‟an, dari sekian ribu ayat di dalamnya, hanya ada 4 ayat yang menjelaskan tentang Isrâ‟ Mi‟raj, yaitu Q.S. Bani Isra`il Ayat 1, dan Q.S. AnNajm Ayat 13 sampai 15. Maksudnya, kebesaran Islam itu bukan terletak pada peristiwa Isra‟ Mi‟raj ini, tapi pada konsep, sistem, dan muatannya. Pada Surat An-Najm Ayat 13-15 itu, menggambarkan bahwa Rasulullah menemui Jibril dalam bentuk aslinya di Sidratil Muntaha ketika Isrâ` Mi‟raj. Sebelumnya Rasulullah juga pernah menjumpai malaikat Jibril dalam bentuk asli ketika menerima ayat pertama (Q.S. Al-Alaq: 1-5) dari Allah S.W.T., yaitu ketika berada di gua Hira. Peristiwa Isrâ' 1 dan Mi'râj merupakan salah satu di antara mukjizat yang diberikan Allah S.W.T. kepada Rasul-Nya, Nabi Muhammad S.A.W., sebagai wujud penghormatan dan pelipur lara setelah paman dan istri beliau meninggal dunia. Peristiwa ini juga sebagai penghibur setelah beliau S.A.W. mendapatkan perlakuan tidak bersahabat dari penduduk Thâif. Peristiwa ini diabadikan dalam AlQur‟ân dan Al-Hadits. Allah S.W.T. menyebutkan peristiwa ini di dua tempat dalam Al-Qur`ân, yaitu Al-Isrâ‟/17 Ayat 1 dan An-Najm/53 Ayat 13-18.